Review on indoor environmental quality parameters towards healthier green buildings in Malaysia / Fadhilah Che Aziz and Md. Yusof Hamid - Fadhilah, Che Aziz; Md. Yusof, Hamid (2015)
This paper presents the review of indoor environmental quality parameters in various guidelines and green rating tools namely; Guidelines on Indoor Environmental Quality for Government Office, Guideline for Performance Evaluation and Office Building‟s Rating, Green Building Index (GBI), Green Real Estate (GreenRE), Green Mark and Building Research Establishment Environment Assessment Method(BREEAM). The review process was done by comparing theparameters existing in these guidelines and green rating tools. Further review has been done on the selected green rating tools across several green policies on indoor environmental quality. Standard references for the parameters isalso identified. Previous studies that have been conducted regarding indoor environmental quality level in several buildings are also been reviewed.With the insights drawn from the comparative review, suggestions on ways to improve indoor environmental quality parameters and assessments are made that may facilitate its implementation. The outcome of the study provides a deep understanding in indoor environment quality parameters and assessments. With the outcome of this study, it may helpsinimprovingassessment in indoor environmental qualitytowards healthier green buildings in Malaysia.